Computational and molecular analysis of conserved influenza A virus RNA secondary structures involved in infectious virion production. Issue 9 (1st September 2016) - Kobayashi, Yuki; Dadonaite, Bernadeta; van Doremalen, Neeltje; Suzuki, Yoshiyuki; Barclay, Wendy S.; Pybus, Oliver G.
ABSTRACT: As well as encoding viral proteins, genomes of RNA viruses harbor secondary and tertiary RNA structures that have been associated with functions essential for successful replication and propagation. Here, we identified stem-loop structures that are extremely conserved among 1, 884 M segment sequences of influenza A virus (IAV) strains from various subtypes and host species using computational and evolutionary methods. These structures were predicted within the 3′ and 5′ ends of the coding regions of M1 and M2, respectively, where packaging signals have been previously proposed to exist. These signals are thought to be required for the incorporation of a single copy of 8 different negative-strand RNA segments (vRNAs) into an IAV particle. To directly test the functionality of conserved stem-loop structures, we undertook reverse genetic experiments to introduce synonymous mutations designed to disrupt secondary structures predicted at 3 locations and found them to attenuate infectivity of recombinant virus. In one mutant, predicted to disrupt stem loop structure at nucleotide positions 219–240, attenuation was more evident at increased temperature and was accompanied by an increase in the production of defective virus particles. Our results suggest that the conserved secondary structures predicted in the M segment are involved in the production of infectious viral particles during IAV replication.